Early and late changes in natural killer cells in response to ledipasvir/sofosbuvir treatment. Issue 4 (1st March 2018) - Golden‐Mason, Lucy; McMahan, Rachel H.; Kriss, Michael S.; Kilgore, Alexandra L.; Cheng, Linling; Dran, Rachael J.; Wieland, Amanda; Rosen, Hugo R.
Abstract : With current direct acting antivirals suppression of HCV viral load is almost universal, however, restoration of innate immune function may not always be the case. Failure to recover NK cell function after successful DAA therapy could have several relevant clinical implications such as, protection from re‐infection and requires further study. Abstract : Chronic hepatitis C virus (HCV) infection is characterized by dysregulated natural killer (NK) cell responses. NKs play a critical role in achieving sustained responses to interferon (IFN)‐α‐based therapy. Rapid sustained HCV‐RNA clearance is now achieved with direct‐acting antivirals (DAAs). Studies of patients receiving first‐wave DAAs suggest NK functional restoration. Here, we investigate the effect of mainstream DAA treatment on NKs. We collected a prospective cohort of male HCV genotype 1‐infected patients treated with ledipasvir/sofosbuvir (n = 22). Peripheral blood was obtained at treatment start, week 2 (W2), W4, W8, and W12 of treatment and 12 weeks posttreatment. Flow cytometry was used to characterize NK responses to therapy. Mean baseline viral load was 1.75 million IU/mL. All subjects rapidly cleared virus and remained HCV RNA‐negative posttreatment. No change was seen in total NK levels; however, the frequency of immature NKs (clusters of differentiation [CD]56 bright ) decreased by W2 and was maintained throughout the study. Phenotypic changes were evident by W2/W4, coincident with rapid viral clearance. At W2, T‐cell immunoglobulin and mucin‐domain containing‐3 and CD161 were significantly increased, returning to pretreatment levels by W12. Some changes were not evident until late (W12 or posttreatment). Down‐regulation of several activation markers, including NKp30 and tumor necrosis factor–related apoptosis‐inducing ligand, was observed at W12 and sustained posttreatment. No difference was observed in IFN‐γ production or cytokine‐mediated killing of NK‐sensitive cell line K562 posttreatment compared to pretreatment. Conclusion : Our phenotype data suggest transient activation followed by dampening of NK cell activity to pretreatment levels. The NK response to ledipasvir/sofosbuvir is not universal in a homogeneous patient cohort. More studies are needed to elucidate the roles of NK cells in IFN‐free regimens, which will have implications for protection from re‐infection and fibrosis progression. ( Hepatology Communications 2018;2:364‐375)